Molecular and genetics approaches for investigation of phospholipase D role in plant cells - Kravets, V.S.; Kolesnikov, Ya.S.; Kretynin, S.V.; Kabachevskaya, E.M.; Liahnovitch, G.V.; Bondarenko, O.M.; Volotovsky, I.D.; Kukhar, V.P. (Вiopolymers and Cell, 2010)
The review is devoted to the analysis of publications concerning the role of phospholipase D (PLD) in regulation of metabolism in plant cells. Analysis of molecular and genetic studies suggest that PLD is an important component of various hormonal and stress signaling pathways.